Phytonutrients: Sources, bioavailability, interaction with gut microbiota, and their impacts on human health - Kan, Juntao; Wu, Feng; Wang, Feijie; Zheng, Jianheng; Cheng, Junrui; Li, Yuan; Yang, Yuexin; Du, Jun (Frontiers in Nutrition, 2022)
Phytonutrients are natural bioactive components present in the daily diet that can exert a positive impact on human health. Studies have shown that phytonutrients may act as antioxidants and improve metabolism after being ingested, which helps to regulate physiological processes and prevent metabolic disorders and diseases. However, their efficacy is limited by their low bioavailability. The gut microbiota is symbiotic with humans and its abundance and profile are related to most diseases. Interestingly, studies have shown that the gut microbiota is associated with the metabolism of phytonutrients by converting them into small molecules that can be absorbed by the body, thereby enhancing their bioavailability. Furthermore, phytonutrients can modulate the composition of the gut microbiota, and therefore improve the host's health. Here, we focus on uncovering the mechanisms by which phytonutrients and gut microbiota play roles in health, and the interrelationships between phytonutrients and gut microbiota were summarized. We also reviewed the studies that reported the efficacy of phytonutrients in human health and the future directions.